Process modelling and life cycle assessment for tongket ali extraction - Foo, Dominic Chwan Yee (Penerbit UTM, 2007)
Computer aided process design (CAPD) tools are commonly used in the chemical process industries since the late 1960’s. However these tools are still relatively new in the biochemical manufacturing sectors. Works on these areas have only been reported in the last one-and-a-half decade (Petrides, 1994; Petrides et al., 1995; Ernst et al., 1997; Evangelista et al., 1998; Koulouris et al., 2000; Rouf et al., 2001; Prazeres and Ferreira, 2004; Tan et al., 2006). In this chapter, the use of CAPD tools, i.e. process simulation and life cycle assessment (LCA) are demonstrated on a phytochemical extraction process. Eurycoma longifolia (more commonly known as Tongket ali) is a tropical herbal plant found in several parts of South East Asia such as Malaysia, Indonesia, and Vietnam. There are four different species of Tongket ali plant, i.e. Eurycoma longifolia, Eurycoma apiculata, Polyathia bullata and Goniothalamus sp (Aziz et al., 2003). Among the four, Eurycoma longifolia is the most commonly used species for the extract production. This plant bears fruit after 2½ years of cultivation while the root is usually taken to be processed after 4 years of cultivation.